Formation of the Institute of Youth Political Elite in the Context of Political Transformation in the Russian Federation - Myasoedova, V A (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2016)
The article discusses the features of the formation of the institute of youth political elite in the Russian Federation. The author proved that the formation of youth political elites directly dependent on the fulfillment of opportunities and professional development of representatives of the youth community and requires a systematic campaign in the formation of the young man and his political socialization. Revealed aspects in the context of which it is necessary to consider the formation of the institute of youth political elite: the socio-economic, political, cognitive. Proposed key methods and forms of interaction between state institutions with the younger generation. The conditions, the implementation of which is necessary for the formation of the institute of youth political elites in Russia: the current administrative and managerial elite has to be aware of the need to create such an elite institution for young people; the existence of regulatory and organizational methods of the activities of youth leaders; a reflection of the youth leader action together communicative interactions; subject-object position of the individual in the current political process of socialization; foster civic political culture, "foundation" which are the concepts of citizenship and patriotism. In conclusion, it is concluded that the development of the political system of education and the building of the Institute of Youth elites should be based on scientific and sociological studies of actual data, reflecting the dynamics of the youth mentality and preferences. A special attention on the part of government actors should be given new urgency to inclusion of young people in the processes of formation of state policy.